The Impact of Teaching Communication Skills to Mothers on Reducing Behavioral Problems in Children with Cerebral Palsy: A Quasi-Experimental Study - Hossein Alibakhshi; Mona Simin ghalamaval; Karim Ayoubi Avaz; Masoomeh Salmani; Aliakbar Pahlavanian; Fatemeh Motaharinezhad; Zahed Kanani (Shiraz University of Medical Sciences, 2023)
Background: Cerebral palsy (CP) affects different aspects of children's development. Some of these negative effects, such as behavioral issues in children, could be mitigated by teaching mothers, as the primary caregivers, the proper skills. The study aims to explore the impact of instructing communication skills to mothers as primary caregivers of children with cerebral palsy (CP) in mitigating behavioral problems exhibited by these children. Methods: In this semi-experimental study, we recruited 42 mothers with children aged 4-10 years diagnosed with cerebral palsy .The mothers were required to be literate, aged between 20 and 40, and their children's mobility score should be at or below 3 in the Gross Motor Function Classification System (GMFCS). Convenient sampling was used for participant selection. The Rutter Children's Behavioral Questionnaire was administered to assess the children's behavioral problems before and after the training. The experimental group participated in nine 90-minute training sessions to improve their communication with their children. In contrast, the control group received no intervention for children's behavioral problems. The collected data were analyzed using Multivariate Analysis of Covariance (MANCOVA). Results: Comparing the mean scores of the two groups in five sub-tests of the Rutter Children's Behavioral Questionnaire revealed significant differences in the following domains: Aggression & hyperactivity, Social incompatibility, Anti-social behaviors, Anxiety & Depression, and General Behavioral problems before the training, indicating variations between the groups (p = 0.001). Following the training, the experimental group significantly reduced all five subtests of Rutter's questionnaire (p = 0.001). Conclusion: The study suggests that equipping mothers with effective communication skills can lead to changes in their interactions with children who have CP and potentially reduce behavioral problems in these children. Consequently, rehabilitation teams may want to consider incorporating communication skills training programs into their overall therapeutic strategies for children with CP.